Pertentangan Rasionalitas Instrumental dan Nilai di Era Covid-19 - Febri Tory; Afrizal Afrizal; Bob Alfiandi (Jurnal Sosiologi Andalas, 2023)
This article discusses the conflict between instrumental rationality and value rationality. The purpose of the article is to re-examine what the differences are between the two and what are the causes of the conflict. The finding shows that contradictory actions would not have occurred if there were no people who had a tendency to place more importance on the dominant rules and were accompanied by the awareness to implement them. The only way to stop it is to "understand" what is behind it to take an action and analyze it from the stability of reality and worldview. Whether reality must be in accordance with the worldview or a worldview that adapts to reality so that there is no mismatch between the two. When reality can no longer be explained by the prevailing worldview. Then the worldview will be reinterpreted so that it can explain reality or vice versa, the reality that must be changed to follow the worldview. Back at this time, the Bukittinggi City Government has unwittingly relaxed the 3M policy (although this rule is still being encouraged in the community) by prioritizing the mandatory wearing of masks and launching the covid-19 vaccination as a new step to stop the spread of the covid-19 outbreak.